Methodological base for transformants representation in nonequilibrium positional uneven-diagonal space - Баранік, Володимир Вікторович; Рябуха, Юрій Миколайович; Леках, Альберт Анатолійович; Стеценко, Оксана Миколаївна; Куліца, Олег Сергійович (Science-based technologies, 2020)
Revealed the method of video data processing at the source level operation conceptual essence, based on the multiagent processing scheme. In the framework of multi-agent approach, the principle of this system operation described in the conditions of necessity to ensure a rapid change of video stream intensity in the process of transmitting video data to end users. An overview of the features of this processing scheme, the principle of intelligent agents functioning and the essence of the processing model are conducted. The general principles of multiagent system functioning are given, considering that each of its functional units is an intellectual agent - a module that performs processing at one particular stage of the general technological process within the framework of basic technology. In other words, an intellectual agent is seen as a set of functions and tools for data processing, and it refers to one or another technological stage of the underlying technology. The essence of application of processing models in the course of video data encoding is revealed, and it is also logically substantiated that such an approach contributes both to reducing the necessary computing resources for the system as a whole and, on the other hand, also contributes to increasing the performance at the same computing capacities. This is achieved, in particular, by dividing the shared resources of the base platform between the individual agents, that is, in this case it is possible to perform parallel computations, and by the fact that the presence of a processing model allows the multiagent system to operate in two modes - the main and the training mode. In the training mode, the system detects regularities between the content features of the video stream fragments that are received for processing, as well as a set of coding parameters for each of the agents, which together will ensure optimal processing. The functioning of the nodes of this system, implemented on the basis of the basic MPEG algorithm is considered.